Pembelajaran Kanji II di Masa Pandemi Covid-19 dengan Bantuan Media Edmodo - Nia Setiawati (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2020)
Abstract The demands of Industrial Revolution 4.0 become a new challenge for teaching and learning activities that must be done via Distance Learning. Covid-19 pandemic causes mostly all lecture classes from different institution to be done online. This matter became authors underly to perform Kanji II course by using various media and learning platforms. This study aims to (1) determine the implemetation of Kanji II course done by using several educational application that shown in Edmodo App, and (2) to find out the responses of students to Kanji II course. The method used in this study is aqualitative descriptive method. Results of the research described that Kanji II course done by giving the kanji learning materials through power point video. The results of this study explains that Kanji II course done by giving the kanji learning materials through power point video. Thereafter for the task, practice, and quiz are given through several application such as Kahoot, Quizizz, and Google Classroom sent via Edmodo. Furthermore, lecturers provide a discourse or reading materials in order to familiarize students to read kanji literation. Thereupon students respond towards Kanji II course are positive. Particularly for the depiction for Kanji learning materials through power point video and the reading materials that provided, helps the students to understand the learning materials well and learning independently. By using several application in task and quiz, it motivates the students to doing the task and generate excitement in cause of competition that happens during the practice and quiz session. Keywords : kanji, edmodo,kahoot, quizizz, google classroom